Abundance of N-cycling genes in an oxygen-deficient upwelling system during La Niña (2018) and El Niño (2019) - Silvia Pajares; Martin Merino; Laura Farías (PANGAEA, 2023)
Seawater samples were collected with 10-L Niskin bottles in four stations along a cross-shore transect in front of the Port of Mazatlán (Mexico) during the oceanographic cruises Maz IV (April 2018) and Maz V (April 2019) on board the R/V "El Puma" (UNAM). Samples for molecular analyses (abundance of N-cycling genes) were collected at different depths based on the oxygen and chlorophyll-a profiles: surface (5 m depth); mixed layer, deep chlorophyll maximum (at 10–45 m depth); oxycline, base of the oxycline (at 60–125 m depth); upper OMZ (only for Maz V); OMZ core (at 250 m depth); and bottom (between 23 m depth in S1 and 670 m depth in S4). Water samples were filtered on board through polycarbonate membranes (0.22-μm pore, Merck Millipore). Genomic DNA was extracted with the DNeasy PowerWater Kit (Qiagen). The abundance of N-cycling genes was assessed using the gene copy number of bacterial and archaeal amoA, anammox bacterial 16S rRNA, nirK, nirS, and nrfA, using a StepOnePlus real-time PCR system (Applied Biosystems).